2019
DOI: 10.22434/ifamr2018.0058
|View full text |Cite
|
Sign up to set email alerts
|

The role of agricultural cooperatives in serving as a marketing channel: evidence from low-income regions of Sichuan province in China

Abstract: Although cooperative organizations aim to enhance agricultural production and marketing, in some countries such as China, not all members sell their products through agricultural cooperatives. This study examines the determinants of using agricultural cooperatives as a marketing channel and its effects on farm income and household income, using survey data collected from cooperative members in low-income regions of Sichuan province in China. We employ both propensity score matching model and inverse probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 34 publications
6
38
0
Order By: Relevance
“…Cooperative membership was also found to be significant for informal retailer and formal wholesale market channels in this study. Cooperatives are considered as a marketing channel used by members (Liu et al, 2018), and this study agrees with Hao et al (2018) who reported a positive influence of cooperative membership in farmers decision to participate in wholesale market channels. Membership of a cooperative is universally understood to provide market access, improve bargaining power and reduce transaction costs for members (Alho, 2015), which are essential to obtain benefits from formal wholesale market channels.…”
Section: Farmer and Farm Specific Factors Influencing Market Channel supporting
confidence: 88%
“…Cooperative membership was also found to be significant for informal retailer and formal wholesale market channels in this study. Cooperatives are considered as a marketing channel used by members (Liu et al, 2018), and this study agrees with Hao et al (2018) who reported a positive influence of cooperative membership in farmers decision to participate in wholesale market channels. Membership of a cooperative is universally understood to provide market access, improve bargaining power and reduce transaction costs for members (Alho, 2015), which are essential to obtain benefits from formal wholesale market channels.…”
Section: Farmer and Farm Specific Factors Influencing Market Channel supporting
confidence: 88%
“…The bulk of family income is made up of off-farm sources. This is in line with the findings of another survey recently carried out in Sichuan Province where the share of farm income just made up about 20% (Liu et al, 2019).…”
Section: Socio-economic Characteristics and Assessment Of Apcs By Comsupporting
confidence: 92%
“…2014; Liu et al . 2019). Membership variable in the fourth column of Table 6 has a positive and statistically significant coefficient, suggesting that for households who are cooperative members, the increase in farm income at the 75th quantile is around 154% ( exp0.933-1false).…”
Section: Resultsmentioning
confidence: 99%